2022
DOI: 10.3390/en15093408
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Aging Models for Electrical Insulation in Power Cables

Abstract: Electrical insulation is an integral part of power components. The aging of electrical insulation is an undeniable fact that limits the operational lifetime of power components. Apart from regular aging, abnormal stresses and the development of defects are real threats because of their contribution in accelerating the aging rate and thereby leading to a premature failure of the power components. Over the decades, various studies have been carried out to understand the aging behavior of electrical insulation ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…where t is time to failure, U r (E) and U b (E) are activation energies for bond formation and breakage. N is the total breakable bonds, n represents bonds already broken, n c is the critical broken bond count leading to failure, and finally h and k B are Planck's and Boltzmann's constants [42]. HV machine design and industry data provide enough evidence to consider failure at time zero as…”
Section: Reliability and Hazard Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…where t is time to failure, U r (E) and U b (E) are activation energies for bond formation and breakage. N is the total breakable bonds, n represents bonds already broken, n c is the critical broken bond count leading to failure, and finally h and k B are Planck's and Boltzmann's constants [42]. HV machine design and industry data provide enough evidence to consider failure at time zero as…”
Section: Reliability and Hazard Functionmentioning
confidence: 99%
“… t=NncknormalBTh()e()Ur(E)kBT(Nn)e()Ub(E)kT(n)10.25emdn $t=\int \nolimits_{N}^{{n}_{\mathrm{c}}}{\left\{\frac{{k}_{\mathrm{B}}T}{h}\left[\left({\mathrm{e}}^{\left(\tfrac{-{U}_{\mathrm{r}}(E)}{{k}_{\mathrm{B}}T}\right)(N-n)}-{\mathrm{e}}^{\left(\tfrac{-{U}_{\mathrm{b}}(E)}{kT}\right)(n)}\right)\right]\right\}}^{-1}\hspace*{.5em}dn$ where t is time to failure, U r ( E ) and U b ( E ) are activation energies for bond formation and breakage. N is the total breakable bonds, n represents bonds already broken, n c is the critical broken bond count leading to failure, and finally h and k B are Planck's and Boltzmann's constants [42]. HV machine design and industry data provide enough evidence to consider failure at time zero as not a typical event, suggesting that the Weibull model should have an offset value.…”
Section: Reliability and Hazard Functionmentioning
confidence: 99%
“…frame stratification [17], -increase in resistance and short circuit in cells [18], -shading of panels [19], -junction box failure [20], -PV panels aging [21], -a fire in the installation caused by a short circuit [22], -degradation of cables insulation [23], -improper operational conditions [24], -no lightning protection or overvoltage [25],…”
Section: Operation and Failures Of Photovoltaic Installationsmentioning
confidence: 99%
“…In this article, dielectric loss tangent (tan δ) of single and series SR and ER specimens have been investigated. Seifert et al (1998) reported dielectric measurements which showed material damages due to electrical overstresses such as those discussed by Choudhary et al (2022) and Ediriweera et al (2020), respectively, and developed an effective tool to detect and classify the ageing in composite polymeric insulations. These were the results of the interactions at the large internal filler surfaces showing an increment in the conductivity and intensification of interfacial polarizations.…”
Section: Introductionmentioning
confidence: 99%